Advances in Neurotechnology, Electronics and Informatics Revised Selected Papers from the 2nd International Congress on Neurotechnology, Electronics and Informatics (NEUROTECHNIX 2014), October 25-26, Rome, Italy - Londral, Ana Rita; Encarnação, Pedro (Biosystems & Biorobotics, 2016)
This book is a timely report on current neurotechnology research. It presents a snapshot of the state of the art in the field, discusses current challenges and identifies new directions. The book includes a selection of extended and revised contributions presented at the 2nd International Congress on Neurotechnology, Electronics and Informatics (NEUROTECHNIX 2014), held October 25-26 in Rome, Italy. The chapters are varied: some report on novel theoretical methods for studying neuronal connectivity or neural system behaviour; others report on advanced technologies developed for similar purposes; while further contributions concern new engineering methods and technological tools supporting medical diagnosis and neurorehabilitation. All in all, this book provides graduate students, researchers and practitioners dealing with different aspects of neurotechnologies with a unified view of the field, thus fostering new ideas and research collaborations among groups from different disciplines.